Apocarotenoids produced from β-carotene by dioxygenases from Mucor circinelloides. Issue 4 (14th February 2019) - Alcalde, Eugenio; Cerdá-Olmedo, Enrique; Al-Babili, Salim
Abstract : Mucor circinelloides exhibits the complex sexual behaviour that is induced in other Mucoromycotina by a family of apocarotenoids called trisporoids. The genome of M. circinelloides contains four genes encoding putative carotenoid cleavage dioxygenases. The gene products of two of them were sufficient to convert β-carotene into the precursors of three families of apocarotenoids, both in vitro and in the Escherichia coli heterologous in vivo system. The first of these products, CarS, cleaved the C40 β-carotene into the C15 precursor of cyclofarnesoids and a C25 apocarotenal that was converted by the second enzyme, AcaA, into the C18 precursor of trisporoids and the C7 precursor of methylhexanoids. Apocarotenoids were not found in single or mixed cultures of the two strains of opposite sex, whose interaction readily produced zygospores, the sexual fusion cells.